The Analysis Effect Of Commodities Crude Oil and Coal In Indonesia Stock Exchange - Hersugondo, H.; Laksana, Rio Dhani; Mayasari, Viviana (Performance, 2019)
Crude oil is a commodity and major world needs today. Since the historic collapse of Lehman Brothers helped precipitate the global economic crisis in the spring of 2008, a strong positive correlation between the price of crude oil continues to appear and the global stock markets, including the stock exchanges in Indonesia. This happens due to capital market investors assume that rising energy prices are a sign of the increasing global demand objective of this study was to determine the effect of crude oil prices and the price of coal on JCI in the Stock Exchange in the period 2012 -2017.          This study will use a time series data analysis tool Vector Autoregression approach. VAR model approach is considered more suitable for detecting a mutual relationship or a dynamic two-way causality between variables in world crude oil prices, the price of gold and the price of coal on the stock price index of the mining sector in the system of equations